Manganese Sulfate Nanocomposites Fabricated by Hot-Melt Extrusion for Chemodynamic Therapy of Colorectal Cancer - Da In Jeong; Sungyun Kim; Ja Seong Koo; Song Yi Lee; Minju Kim; Kwang Yeol Kim; Md Obyedul Kalam Azad; Mrinmoy Karmakar; Seongnam Chu; Byung-Jo Chae; Wie-Soo Kang; Hyun-Jong Cho (Pharmaceutics, 2023)
The development of metal salts-based nanocomposites is highly desired for the Fenton or Fenton-like reaction-based chemodynamic therapy of cancer. Manganese sulfate (MnSO4)-dispersed nanoparticles (NPs) were fabricated with a hot-melt extrusion (HME) system for the chemodynamic therapy of colorectal cancer in this study. MnSO4 was homogeneously distributed in polyethylene glycol (PEG) 6000 (as a hydrophilic polymer) with the aid of surfactants (Span 80 and Tween 80) by HME processing. Nano-size distribution was achieved after dispersing the pulverized extrudate of MnSO4-based composite in the aqueous media. The distribution of MnSO4 in HME extrudate and the interactions between MnSO4 and pharmaceutical additives were elucidated by Fourier-transform infrared, X-ray diffractometry, X-ray photoelectron spectroscopy, and scanning electron microscopy analyses. Hydroxyl radical generation efficiency by the Fenton-like chemistry capability of Mn2+ ion was also confirmed by catalytic assays. By using the intrinsic H2O2 in cancer cells, MnSO4 NPs provided an elevated cellular reactive oxygen species level, apoptosis induction capability, and antiproliferation efficiency. The designed HME-processed MnSO4 formulation can be efficiently used for the chemodynamic therapy of colorectal cancer.